Modern irrigation technologies and their role in the agricultural expansion of wheat crop production (Holy Karbala Governorate as a model (Journal of the College of Basic Education, 2022)
This study is based on the knowledge of the most important modern irrigation technologies used in the cultivation and production of the wheat crop in the holy Karbala governorate and the extent of its role in the agricultural expansion of its production as well as knowing the extent to which it provides the quantities of water used when compared to traditional irrigation methods, through which it may be found that the most important irrigation techniques are The modern used in the production of the wheat crop is (constant and pivotal sprinkler irrigation). The volume of water consumption in the areas used for modern irrigation technologies was less than the volume of water consumption of traditional irrigation methods by (67%). If we used modern irrigation methods instead of traditional irrigation methods in the study area We will be able to provide quantities of water for an area of ​​(9846) dunams, and the reason for this is due to the efficiency of modern irrigation methods through which it is possible to control the amount of added water that is difficult to control when using traditional irrigation methods, in addition to its advantage in the absence of waste. Of water when transported from the source to the field, because it is through pipes, while the water is transported by traditional irrigation methods through the lined or open earthen channels, which because of them in In both cases, the water is exposed to evaporation and exudation, in addition to a quantity of water absorbed from plants and weeds that grow in these channels. As a result of the irrigation efficiency of these modern technologies, this helped expand the area cultivated with wheat in them, while the area cultivated with wheat was estimated at (16370) dunums during the agricultural season (2010-2011), which is the first season for the use of modern irrigation methods ( Sprinkler irrigation), it became estimated at (66924) dunums during the agricultural season (2018-2019) and as a result the quantity of production increased significantly, as it reached (68713) tons after it reached (9586) tons during the agricultural season (2010-2011).